Mad on Radium : New Zealand in the Atomic Age. - Priestley, Rebecca (Auckland University Press, 2012)
Although New Zealander Lord Rutherford was the first to split the atom, the country has since been known around the world for its nuclear-free stance. In this engaging and accessible book, an alternative history is revealed of ""nuclear New Zealand""--When there was much enthusiasm for nuclear science and technology. From the first users of X-rays and radium in medicine to the plans for a nuclear power station on the Kaipara Harbour, this account uncovers the long and rich history of New Zealanders' engagement with the nuclear world and the roots.